Trace inequalities for logarithms and powers of J-Hermitian matrices - Bebiano, N.
Spectral inequalities are stated for the trace of the exponential or the logarithmic of certain J-Hermitian matrices, J = Ir ⊕ - In - r, 0 < r < n . The obtained inequalities are established in the context of indefinite inner product spaces, and they are known to be valid for Hilbert space operators or operator algebras. © 2010 Elsevier Inc. All rights reserved.